Local peribulbar anesthesia before glaucoma filtering surgery in a patient with Brugada syndrome. Issue 2 (March 2021) - Loiudice, Pasquale; Monitillo, Francesco; Nardi, Marco; Iacoviello, Massimo; Casini, Giamberto
We report anesthetic management in a patient with Brugada syndrome, an inherited syndrome characterized by normal QT interval, typical ST-segment–elevation in the right precordial leads, and increased risk of sudden cardiac death in the absence of myocardial ischemia or structural heart disease. A 69-year-old man scheduled for glaucoma filtering surgery underwent local peribulbar anesthesia using 5 mL of lidocaine 20 mg/mL solution that was slowly injected into two different sites approximately 10 min prior to the surgical procedure. The surgery proceeded uneventful and data of patient's blood pressure, heart rate, oxygen saturation were collected. Continuous electrocardiography monitoring before, during, and up to 6 h after surgery did not reveal any arrhythmia or tachycardia. A certain number of drugs should be avoided in patients with Brugada syndrome because of their potential risk to trigger an arrhythmia. Among them there are some anesthetics and in particular those that are sodium channel blockers. Ropivacaine and bupivacaine, commonly used for peribulbar block, have been associated with onset of severe arrhythmias. Contrarily, the use of class IB drugs mexiletine and lidocaine is generally considered safe. Local anesthetic agent should be carefully chosen, and anesthesia should be obtained using the minimal necessary drug dose.